2015
DOI: 10.4314/ijbcs.v9i4.24
|View full text |Cite
|
Sign up to set email alerts
|

Hygienic quality of ready-to-eat salads sold in the street and a modern restaurant in Lomé, TOGO

Abstract: Poisoning following salads consumption was often reported in Lomé. This study was carried out to evaluate contamination of salads sold in Lomé. Sixty salad samples from modern restaurant (Domino), seventy from street sellers and forty of fresh vegetables from two markets were randomly collected. Microbiological quality of samples was examined on the basis of AFNOR methods and criteria. Salad selling occurs in room temperature. That modern restaurant uses cold to preserve foods. Microbial analyzes revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
1
7
1
Order By: Relevance
“…These results are contrary to those of Soncy et al [30] in Togo and Antwi-Agyei et al (2015 [31]) in Ghana, which obtained much higher loads of 2.5 × 10 3 CFU/g (3.4 log 10 CFU/g) and 4.23 log 10 CFU/g, respectively, with a prevalence of 22.8% and 98%. Similarly, Barrada et al [32] in Morocco and Amposah et al [33]) in Ghana had obtained respectively 99.3% and 100% raw vegetable salads unsatisfactory microbiological quality.…”
Section: Discussioncontrasting
confidence: 56%
“…These results are contrary to those of Soncy et al [30] in Togo and Antwi-Agyei et al (2015 [31]) in Ghana, which obtained much higher loads of 2.5 × 10 3 CFU/g (3.4 log 10 CFU/g) and 4.23 log 10 CFU/g, respectively, with a prevalence of 22.8% and 98%. Similarly, Barrada et al [32] in Morocco and Amposah et al [33]) in Ghana had obtained respectively 99.3% and 100% raw vegetable salads unsatisfactory microbiological quality.…”
Section: Discussioncontrasting
confidence: 56%
“…These foods analyzed are excessively loaded with Coagulase-positive staphylococci, it is sufficient proof of lack of personal hygiene. Our results are similar to other studies in the same direction (Mensah et al, 2002;Barro et al, 2002;Christison et al, 2007;Ahoyo et al, 2010;Sadık et al, 2014;Ashraf et al, 2014;Kassé et al, 2014;Ogunyemi et al, 2015;Soncy et al, 2015). These results could be explained by the fact that most of the food handlers do not use hair net, gloves and other protective gear when preparing and serving.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with the current findings, Khater et al [35] in Egypt documented that salad samples obtained from restaurants had a higher ACC value than the street-vended ones (5.70 and 4.92 log CFU/g, respectively). In contrast to these results, in Togo, Soncy et al [36] reported that the microbial loads of salad samples from the street vendors in Lomé were higher than that of the studied Domino restaurant.…”
Section: Discussionmentioning
confidence: 59%
“…were not detected in their samples: Soncy et al [36] in Togo, Allen et al [38] in Canada, Caponigro et al [39] in Italy and earlier, Sagoo et al [8] in the UK. It has been documented that negative results may suggest that levels of occurrence of these pathogens on the sampled population of RTES may be below the sensitivity of the used detection method and could be minimally affected by season and other considered factors [39] .…”
Section: Discussionmentioning
confidence: 91%